Congenital esophageal stenosis: a rare case of dysphagia - Serrão, E (2012)
Congenital esophageal stenosis (CES) is a rare anomaly, resulting from incomplete separation of the respiratory tract from the primitive foregut at the 25th day of life. First clinical signs are abnormalities of the swallowing mechanism caused by the intrinsic narrowing of the esophagus. Diagnosis is usually delayed, requiring an accurate history and high level of suspicion, alongside with an esophagogram. Definite diagnosis is only confirmed by histological examination. Treatment usually involves surgery, depending on the severity, location and type of stenosis. We report the case of an 18 months old toddler diagnosed with CES. The characteristic radiographic and CT features are presented as well as the histology.